Hepatotoxicity of Antimycotics Used for Invasive Fungal Infections: In Vitro Results. (4th April 2017) - Doß, Sandra; Potschka, Heike; Doß, Fanny; Mitzner, Steffen; Sauer, Martin
Abstract : Purpose. Drug-induced liver injury (DILI) is the most common cause of liver injury and a serious clinical problem; antimycotics are involved in approximately 3% of all DILI cases. The hepatotoxicity of many drugs, including the antimycotics, is poorly screened in human models. Methods. In a standardized assay the cytotoxicity on hepatocytes of different concentrations (C max, 5x C max, and 10x C max) of the antimycotics used for systemic infections was tested. Anidulafungin (ANI), liposomal amphotericerin B (L-AmB), caspofungin (CASPO), fluconazole (FLUCO), and voriconazole (VORI) were incubated with HepG2/C3A cells. After incubation, the viability of cells (XTT test, LDH release, trypan blue staining), the synthesis of albumin, the cytochrome 1A2 activity, and the cell death (DNA fragmentation) were determined. Kruskal-Wallis and Mann–Whitney tests were used for statistical analyses. Results. L-AmB, ANI, and CASPO showed a mild hepatotoxicity in the C max concentrations. Higher concentrations of anidulafungin led to a severe impairment of hepatocyte viability and function. The azoles FLUCO and VORI had a higher hepatotoxic potential in all concentrations. Conclusion. Antimycotics, especially azoles, used for systemic infections should be given with caution in patient with liver insufficiency or liver failure or high risk for this; therefore, therapeutic drug monitoring should be used. Further studies with this approach are encouraged.